Diversity in rhizospheric microbial communities in tea varieties at different locations and tapping potential beneficial microorganisms - Zhang, Zheng; Ge, ShiBei; Fan, Li-Chao; Guo, Shuai; Hu, Qiang; Ahammed, Golam Jalal; Yan, Peng; Zhang, Li-Ping; Li, Zheng-Zhen; Zhang, Jian-Yang; Fu, Jianyu; Han, Wenyan; et al. (Frontiers in Microbiology, 2022)
Soil microenvironments and plant varieties could largely affect rhizosphere microbial community structure and functions. However, their specific effects on the tea rhizosphere microbial community are yet not clear. Beneficial microorganisms are important groups of microbial communities that hold ecological functionalities by playing critical roles in plant disease resistance, and environmental stress tolerance. Longjing43 and Zhongcha108 are two widely planted tea varieties in China. Although Zhongcha108 shows higher disease resistance than Longjing43, the potential role of beneficial tea rhizosphere microbes in disease resistance is largely unknown. In this study, the structure and function of rhizosphere microbial communities of these two tea varieties were compared by using the Illumina MiSeq sequencing (16S rRNA gene and ITS) technologies. Rhizosphere soil was collected from four independent tea gardens distributed at two locations in Hangzhou and Shengzhou cities in eastern China, Longjing43 and Zhongcha108 are planted at both locations in separate gardens. Significant differences in soil physicochemical properties as demonstrated by ANOVA and PCA, and distinct rhizosphere microbial communities by multiple-biotech analyses (PCoA, LEfSe, Co-occurrence network analyses) between both locations and tea varieties (p<0.01). Functions of bacteria were annotated by the FAPROTAX database, and a higher abundance of Nitrososphaeraceae relating to soil ecological function was found in rhizosphere soil in Hangzhou. LDA effect size showed that the abundance of arbuscular mycorrhizal fungi (AMF) was higher in Zhongcha108 than that in Longjing43. Field experiments further confirmed that the colonization rate of AMF was higher in Zhongcha108. This finding testified that AMF could be the major beneficial tea rhizosphere microbes that potentially function in enhanced disease resistance. Overall, our results confirmed that locations affected the microbial community greater than that of tea varieties, and fungi might be more sensitive to the change in microenvironments. Furthermore, we found several beneficial microorganisms, which are of great significance in improving the ecological environment of tea gardens and the disease resistance of tea plants. These beneficial microbial communities may also help to further reveal the mechanism of disease resistance in tea and potentially be useful for mitigating climate change-associated challenges to tea gardens in the future.